Correlation of energy and protein intake with nitrogen balance changes in late acute phase critically ill patients - Githa Putri Puspita Sari; Witjaksono, Fiastuti; Sutanto, Krisadelfa; Singal, Anna Maurina (Indonesian Nutrition Association, 2025)
Background: The hypercatabolic process due to metabolic stress in critically ill patients, especially in the acute phase, is very high, causing protein degradation. Inadequate intake and high protein losses will result in a negative nitrogen balance. Objective: To analyze the correlation of energy and protein intake in the late acute phase with nitrogen balance changes. Methods: This study’s method was cross−sectional with consecutive sampling, conducted in the ICU of the university of Indonesia hospital. Energy and protein intake were assessed for 7 days. On days 3 and 7 of treatment, 24−hour urine urea nitrogen levels and nitrogen balance (NB) were assessed. Twenty three subjects participants in this study. Results: There was a positive correlation between energy and protein intake with NB on day 3 (r=0.5, p=0.01 ;r=0.6, p=0.003). The mean nitrogen balance changes was positive, namely 3.8 g. There was a significant correlation between energy and protein intake with NB changes (p>0.01) Conclusion: Energy and protein intake were positively correlated with nitrogen balance in the early acute phase. The results show that the administration of energy and protein starting at low intake in the early acute phase and gradually reaching the target intake during the late acute phase leads to an improvement in nitrogen balance.